467 EFFECT OF INDOMETHACIN AND IBUPROFEN ON RAT LUNG VASCULAR ENDOTHELIAL GROWTH FACTOR AND SOLUBLE VASCULAR ENDOTHELIAL GROWTH FACTOR RECEPTORS DURING EARLY POSTNATAL DEVELOPMENT. (1st January 2006) - Gharraee, Z.; Beharry, K. D.; Hasan, J.; Abad-Santos, P.; Jan, A.; Sills, J. H.; Aranda, J. V.; Modanlou, H. D.
Abstract : Vascular endothelial growth factor (VEGF) is a potent endothelial cell mitogen that is highly involved in lung microvasculature proliferation, permeability, and maturation. Its overexpression in the neonatal lung results in pulmonary hemorrhage and inflammation. Soluble VEGF receptors (sVEGFR-1, sVEGFR-2) are the negative regulators in the VEGF signaling pathway. Indomethacin (Indo) is administered to premature newborn infants for ductus arteriosus closure. However, its use is associated with increased pulmonary vascular resistance. The purpose of this study was to compare the effects of early administration of Indo and Ibu on VEGF and its soluble receptors in the developing rat lungs. Sprague-Dawley rats received IP injections at birth (P0), postnatal day 1 (P1), and P2 of either saline (Sal); 0.2 mg/kg IN on P0 followed by 0.1 mg/kg on P1 and P2; 1.0 mg/kg IN on P0 followed by 0.5 mg/kg on P1 and P2; 10 mg/kg IB on P0 followed by 5 mg/kg on P1 and P2; and 50 mg/kg IB on P0 followed by 25 mg/kg on P1 and P2. At P14 and P21 (time of microvascular maturation), lung homogenates were assessed for VEGF, sVEGFR-1 and sVEGFR-2. Untreated term rat lungs were also examined. VEGF levels increased at P14 and P21 ( p < .001 vs term) whereas sVEGFR-1 levels remained unchanged and were 30- to 50-fold higher than sVEGFR-2. sVEGFR-2 levels peaked at P14 (p < .001 vs term) and decreased at P21 (p < .01 vs. term and P14). Indo and Ibu had no effect on VEGF levels at P14; however, at P21, VEGF levels increased with low-dose Indo (p < .05 vs Sal). Similarly, sVEGFR-1 levels remained unchanged at P14. In contrast, sVEGFR-1 levels were elevated at P21 in the high-dose Indo group (p < .001 vs low-dose Ibu and Indo). Low and high doses of Indo had significant suppressive effects on VEGFR-2 at P14 (p < .01 vs Sal), although the effect of Indo was more potent and was sustained until P21 (p < .01 vs Sal). Soluble VEGFR-2 may play an important role during the time of lung microvascular maturation. Its suppression at P21 with Indo may result in VEGF overexpression. Ibu does not exhibit similar suppressive effects at this crucial time of lung development and therefore should be considered as an alternate therapy for ductus arteriosus closure.